State suppression of trade unions — overt and covert, old and new. (1st June 2022) - Smith, Dave
Abstract : When even the BBC have criticised the handling of the Sarah Everard vigils by the Metropolitan Police, and flag waving patriots in the Labour Party oppose the Johnson government's proposed legislation, you begin to realise the extent of the drift towards authoritarianism. The Police, Crime and Sentencing Bill is just one such example The UK political police units also send their officers to work undercover within the labour movement. And they cultivate informants within the trade union movement itself, enabling them to supply employers with the information needed to identify and then blacklist progressive trade union activists. Sharon Graham's pledge to uncover the truth about any collusion by UNITE officials in blacklisting is therefore to be welcomed. Marxists, especially those active in the labour movement, should be outraged by the drift towards authoritarianism by the British state, but not surprised. Fortunately, young people have turned out in their thousands at Kill The Bill protests against the Tories' proposed new authoritarian laws, though, and unions are beginning to rediscover the more muscular organising methods of the past.